2018
DOI: 10.1039/c8cp02599a
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved FTIR study of light-driven sodium pump rhodopsins

Abstract: Light-driven sodium ion pump rhodopsin (NaR) is a new functional class of microbial rhodopsin. A previous flash photolysis study of Krokinobacter eikastus rhodopsin 2 (KR2) revealed the presence of three kinetically distinct intermediates: K, L/M, and O. Previous low-temperature Fourier-transform infrared (FTIR) spectroscopy of KR2 showed that photoisomerization from the all-trans to the 13-cis form is the primary event of the Na+ pumping photocycle, but structural information on the subsequent intermediates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 47 publications
2
33
3
Order By: Relevance
“…3). Surprisingly, all-trans configuration of the retinal in the O-state is in contrast to the recently published timeresolved Fourier-transform infrared spectroscopy (FTIR) data, where authors suggested 13-cis configuration in the O-state of NaRs 21 , but is in line with the data on another light-driven Na + pump from Gillisia limnaea (GLR), published in 2014, where the authors report a distorted all-trans configuration of retinal in the O-state 22 . In ref.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…3). Surprisingly, all-trans configuration of the retinal in the O-state is in contrast to the recently published timeresolved Fourier-transform infrared spectroscopy (FTIR) data, where authors suggested 13-cis configuration in the O-state of NaRs 21 , but is in line with the data on another light-driven Na + pump from Gillisia limnaea (GLR), published in 2014, where the authors report a distorted all-trans configuration of retinal in the O-state 22 . In ref.…”
Section: Resultscontrasting
confidence: 98%
“…This distortion may result in the appearing of the peak at 940 cm −1 described in ref. 21 . We also cannot exclude that the inconsistency of the results on the retinal configuration in the O-state may originate from the different conditions and protein environment during the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly in terms of function, KR2 in treated crystals follows a photocycle (Fig. 1) identical to that observed by our absorption spectroscopy on purified KR2 in agreement with previous reports 19,18 .…”
Section: Photocycle In Kr2 Crystalssupporting
confidence: 92%
“…The pumping cycle of KR2 has been studied by a variety of time-resolved spectroscopic techniques 1,[13][14][15][16][17][18][19] . High-resolution structures of the resting state have been determined in various forms by X-ray crystallography 2,3,20 .…”
Section: Introductionmentioning
confidence: 99%
“…While at first, it was modeled as an unbranched unidirectional photocycle with five distinct photointermediates, 14 later on more complex models were proposed. 15,16,17 KR2's photocycle has already been studied extensively with various techniques [18][19][20][21][22][23] but still remains to be understood completely. Especially the spectral location of the photointermediates, as well as the equilibria within the photocycle remain elusive.…”
Section: Introductionmentioning
confidence: 99%